Research Progress of Natural Product Photosensitizers in Photodynamic Therapy - Zhou, Xiaoxia; Ying, Xufang; Wu, Linjie; Liu, Liqin; Wang, Ying; He, Ying; Han, Min (Planta Medica, 2024)
Photodynamic therapy is a noninvasive cancer treatment that utilizes photosensitizers to generate reactive oxygen species upon light exposure, leading to tumor cell apoptosis. Although photosensitizers have shown efficacy in clinical practice, they are associated with certain disadvantages, such as a certain degree of toxicity and limited availability. Recent studies have shown that natural product photosensitizers offer promising options due to their low toxicity and potential therapeutic effects. In this review, we provide a summary and evaluation of the current clinical photosensitizers that are commonly used and delve into the anticancer potential of natural product photosensitizers like psoralens, quinonoids, chlorophyll derivatives, curcumin, chrysophanol, doxorubicin, tetracyclines, Leguminosae extracts, and Lonicera japonica extract. The emphasis is on their phototoxicity, pharmacological benefits, and effectiveness against different types of diseases. Novel and more effective natural product photosensitizers for future clinical application are yet to be explored in further research. In conclusion, natural product photosensitizers have potential in photodynamic therapy and represent a promising area of research for cancer treatment.
Keywords: photodynamic therapy; natural product; photosensitizers; cancer